Different oscillatory rhythms anticipate failures in executive and arousal vigilance - Luna, Fernando G.; Aguirre, María Julieta; Martín-Arévalo, Elisa; Ibáñez, Agustín; Lupiáñez, Juan; Barttfeld, Pablo (Frontiers in Cognition, 2023)
Introduction. Vigilance is the challenging ability to maintain attention during long periods. When performing prolonged tasks, vigilance failures are often observed, reflecting a decrease in performance. Previous research has shown that changes in oscillatory rhythms are associated with states of vigilance loss. The present study aimed to investigate whether changes in different oscillatory rhythms anticipate failures in two vigilance components: (a) executive vigilance –necessary to detect infrequent critical signals– and (b) arousal vigilance –necessary to maintain a fast reaction to environmental stimuli without much control–. Methods. 37 young adults (age: M = 25.86; SD = 4.99) completed two experimental sessions in which high-density electroencephalography signal was recorded while they performed the Attentional Networks Test for Interactions and Vigilance – executive and arousal components, a task that simultaneously measures executive and arousal vigilance along with others attentional functions. Changes in delta, theta, alpha, beta, and gamma power before target onset were analyzed at the trial level in the executive and the arousal vigilance subtasks and as a function of the behavioral response. Results. Changes in different oscillatory rhythms were observed prior to failures in executive and arousal vigilance. While increased alpha power in left occipital regions anticipated misses in the executive vigilance subtask, increased delta power in frontal-central regions anticipated very slow responses in the arousal vigilance subtask. Discussion. The present results further support an empirical dissociation at the neural level between executive and arousal vigilance. Changes in alpha –in left occipital regions– and delta –in frontal-central regions– power might be identified as different brain states associated with loss in vigilance components when performing prolonged tasks.